2013
DOI: 10.1371/journal.pone.0077760
|View full text |Cite
|
Sign up to set email alerts
|

Not All Is Lost: Old Adults Retain Flexibility in Motor Behaviour during Sit-to-Stand

Abstract: Sit-to-stand is a fundamental activity of daily living, which becomes increasingly difficult with advancing age. Due to severe loss of leg strength old adults are required to change the way they rise from a chair and maintain stability. Here we examine whether old compared to young adults differently prioritize task-important performance variables and whether there are age-related differences in the use of available motor flexibility. We applied the uncontrolled manifold analysis to decompose trial-to-trial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 46 publications
5
66
4
2
Order By: Relevance
“…Previous studies on STS using the UCM analysis have adopted the head position, hand position 6) , ground reaction force 11) , and linear and angular momentum of COM 10) as the performance variables. The STS is characterized by three essential components, namely, (a) generating sufficient joint torque needed to rise (progression), (b) ensuring stability by moving the COM from a large BOS to a narrow BOS defined solely by the feet (stability), and (c) the ability to modify movement strategies used to achieve these goals depending on environmental constraints ( adaptation ) 3 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on STS using the UCM analysis have adopted the head position, hand position 6) , ground reaction force 11) , and linear and angular momentum of COM 10) as the performance variables. The STS is characterized by three essential components, namely, (a) generating sufficient joint torque needed to rise (progression), (b) ensuring stability by moving the COM from a large BOS to a narrow BOS defined solely by the feet (stability), and (c) the ability to modify movement strategies used to achieve these goals depending on environmental constraints ( adaptation ) 3 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The first phase is required for simultaneous COM deceleration in the horizontal direction and COM acceleration in the vertical direction. Greve et al 11) reported that older adults employed greater motor flexibility, stabilizing both horizontal and vertical movement of COM during STS. However, Scholz et al 9 ) reported that joint movement showed no kinematic synergy stabilizing the vertical path of COM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during sit to stand, do joint motions organize synergistically to stabilize the center of mass, the center of pressure, or the position of the head? 23,24 . In other words, the method allows the investigation of which performance variable is being prioritized by the control mechanisms.…”
Section: Investigating Synergies With Ucm In Populations With Movemenmentioning
confidence: 99%
“…The uncontrolled manifold (UCM) method is a well-established approach to assessing the coordination of multiple degrees of freedom (DoF) in synergies that stabilize performance in human actions. The method has been applied to a variety of actions, such as sit-to-stance, finger-force production, and goal-directed reaching (Black, Smith, Wu, & Ulrich, 2007;Domkin, Laczko, Djupsjöbacka, Jaric, & Latash, 2005;Greve, Zijlstra, Hortobágyi, & Bongers, 2013;Klous, linear model is created by entering the joint angles as independent variables and the index-finger position as the dependent variable. Their relative relationships are described in the regression equations (see Equation 1; a separate equation is used for each direction of the fingertip position).…”
mentioning
confidence: 99%